Measuring board diversity: A systematic literature review of data sources, constructs, pitfalls, and suggestions for future research - Hendrik Behlau; Janice Wobst; Rainer Lueg (Corporate Social Responsibility and Environmental Management, 2023)
The purpose of this systematic literature review is to provide a comprehensive overview of the methods used to measure board diversity. We develop a framework to structure empirical studies and develop an agenda for future research. We selected 61 empirical articles from an initial sample of 1035. This study discusses the different data collection methods. We group director and board attributes into the constructs of structural, demographic, and cognitive diversity. We identify four different approaches to combining and measuring diversity: non-index, single-index, cross-indices, and inter-indices. We find that measuring board diversity requires a mixture of archival and primary research, as well as various methods such as applying indices, constructing heterogeneity scores, and using machine learning approaches to infer directors' attributes. We contribute to research by providing a framework that structures measuring techniques for board diversity, a future research agenda, and insights on potential window-dressing.
Keywords: 650; board attributes; board diversity; cognitive characteristics; measurement; structural characteristics; systematic literature review